Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.053
|View full text |Cite
|
Sign up to set email alerts
|

Why I Retweet? Exploring Users Perspective on Decision-Making of Information Spreading during Disasters

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…The results indicate that more users tend to gather and share information from other online users (rather than replying to posts) during the disruptive event. Although reply and mentions also contribute to network growth on social media in normal situations, as reported in existing studies (Abdullah et al 2017;Kogan et al 2015;Metaxas et al 2015a), we find that the primary activity contributing to network growth in crises situations is sharing. In crisis situations, people actively search for situational information and when they find useful information, they tend to share it.…”
Section: Types Of Activitiessupporting
confidence: 68%
“…The results indicate that more users tend to gather and share information from other online users (rather than replying to posts) during the disruptive event. Although reply and mentions also contribute to network growth on social media in normal situations, as reported in existing studies (Abdullah et al 2017;Kogan et al 2015;Metaxas et al 2015a), we find that the primary activity contributing to network growth in crises situations is sharing. In crisis situations, people actively search for situational information and when they find useful information, they tend to share it.…”
Section: Types Of Activitiessupporting
confidence: 68%
“…This is consistent with our findings in that the proportion of anxiety retweets was double that of the raw tweets. Abdullah, Nishioka, Tanaka, and Murayama (2017) found that a tweet is more likely to get retweeted if the information in a tweet is seen as credible, important, interesting, or could garner a high amount of interest or further retweets. As a result, social media hype is generated.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SMN, users might, for instance, want to provide others with timely and presumably relevant information about an uncertain event, such as a natural disaster (e.g., Abdullah et al 2017;. Biased agents' behavior can thus be interpreted as a function of their individual motives rather than as attempts to achieve some sort of collective outcome, and without implying a normative judgment.…”
Section: Model Formulationmentioning
confidence: 99%